Dye removal from synthetic and dye bath wastewater by electrocoagulation method and isotherms - Tuba Öztürk; Hande Akbaş; Gülşen Aydın Keskin (MANAS: Journal of Engineering)
This study investigated the treatment of authentic wastewater taken from a dye bath and synthetic wastewater by electrocoagulation. Experiments were conducted by determining the optimum treatment conditions using Al and Fe electrodes. The optimum current, pH and initial dye concentration in the synthetic wastewater (SW) for the Al electrodes were 8A, 7.57 and 50 mg/L, respectively, while these for the Fe electrodes were 8A, 9 and 100 mg/L, respectively. The optimum current, pH and thinning rate were seen in the dye bath wastewater (DBW) for the Al electrodes as 8A, 8 and 1/60 and for the Fe electrodes as 8A, 9 and 1/30, respectively. While carrying out the experiments using these experimental conditions, color and COD removal from SW and DBW with long-running treatments was investigated. Moreover, it was determined that the Langmuir isotherm model was more convenient for the experimental data in the process. In the last part of the study, a correlation analysis was carried out between color and COD removal. Besides, the efficiencies for the use of Al and Fe electrodes respectively for both color and COD removal were compared, and comments were made for different groups by one-way ANOVA.